(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ramli R, Zulkifli NFD, Ismail A, Pardi F. 2025. Monsoonal effects on meiofaunal assemblages in Pulau Tuba Mangroves, Langkawi, Malaysia. Biodiversitas 26: 4694-4705. Mangrove ecosystems are dynamic coastal habitats that support diverse and functionally important benthic communities, including meiofauna. This study investigates the spatial and temporal patterns of meiofaunal assemblages in the mangrove sediments of Pulau Tuba, Langkawi, Malaysia, in relation to monsoonal-driven environmental changes. Sediment and porewater samples were collected from four stations (MG1-MG4) in June 2023 and November 2023 to represent the Southwest Monsoon and Northeast Monsoon, respectively. Meiofauna were collected and classified to major taxa, while various environmental parameters were quantified, including salinity, temperature, pH, dissolved oxygen, organic matter content, sediment grain size, and composition. A total of nine meiofaunal groups were recorded, namely Sarcomastigophora, Copepoda, Rotifera, Oligochaeta, Halacaroidea, Polychaeta, Ostracoda, Kinorhyncha, with Nematoda dominated (>90%) in both seasons. Meiofaunal density was significantly higher during the Southwest Monsoon (Paired t-test, p<0.05). Diversity indices showed low species diversity, with dominance by a few groups. Multivariate analyses revealed that seasonal variation had a greater influence on community structure than spatial differences. Principal Component Analysis and Distance-based redundancy analysis identified salinity, temperature, organic matter, and dissolved oxygen as the key environmental drivers structuring meiofaunal communities. These findings add to the limited body of research on Malaysian and tropical mangrove meiofauna and provide observational evidence that may inform conservation planning, sustainable management, and policy discussions aligned with SDGs 14 and 15.